Solution of Linearized Flat Problem of Hydrodynamics (IVF) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In the present paper a method of the generalized potential to planes is applied for the solution of the linearized according to Oseen of flat problem of hydrodynamics incompressible viscous fluid (IVF). Generalized potential simple layer containing McDonald function serves kernel for generalized potential to planes. For finding of an unknown density of the potential simple layer is received linear integral equation, containing double integral from curvilinear integral along border of the streamlined area. Sharing the pressure is in turn defined by potential simple layer with density of the potential, determined by linear integral equation, hanging from solution specified above integral equation. The offered method of the successive iterations, allowing elaborate the solution of the problem before achievement given to accuracy. As example of exhibit to theories is considered solution of the problem theory of hydrodynamic greasing.